Performance of Commercial Television Stations as an Outcome of Interorganizational Linkages and Environmental Conditions - Stearns, Timothy M.; Hoffman, Alan N.; Heide, Jan B. (Academy of Management Journal, 1987)
This study explored the effects of interorganizational linkages as a moderator between organizational performance and environmental conditions. Analyses covered 145 commercial television stations in 25 markets over a 15-year period. Results indicated that interorganizational linkages can serve to protect television stations from adverse effects of environmental complexity and scarcity, but that uncertainty has a direct effect on the performance of a station.